Comparative study of modified open technique and closed technique for primary trocar insertion in laparoscopic surgery - Bathla, Vikas; Thekdi, Pukur I.; Koradia, Pratik; Jhala, Dushyantsinh; Gadhvi, Udit (International Journal of Research in Medical Sciences, 2016)
Background: The objective of this study was to compare the safety and efficacy of modified open technique and closed technique for gaining entry [primary trocar insertion] and establishing pneumoperitoneum in laparoscopic surgery. Methods: The present study was prospective, observational and longitudinal. Protocol of the procedure was formed along with Performa, Patient Information Sheet and Informed Consent Form. The present study was carried out in surgery department of C.U Shah medical college, Surendranagar, Gujarat state. The study was carried out from 1st October 2012 till 31st May 2014. A total of two hundred patients undergoing emergency and elective laparoscopic surgery were included in our study. Case records of patients was recorded in the Performa containing demographic details, size and site of trocar insertion, technique of trocar insertion, intraoperative, early postoperative and late post operative complications were noted. Results: Total of 200 cases was included in our study. The age of patients ranges from 10-70 years. Out of 200 cases 90% were females suffering from different ailments and 105 were males in group A while in Group b 80% were females and 20%were males. In terms of on table complications; gastrointestinal injury is more in close method of trocar insertion. Conclusions: We would advocate the modified open technique of trocar insertion as a technique of choice in primary trocar insertion as it is more efficacious and counts more on patient safety as compared to the close technique.